Assessment of Factors Limiting Advanced Technology Adoption in Maize Cultivation in Uganda: A Case Study of Kabale District South Western Uganda. - Asiimwe, Moses (Kabale University, 2024)
This study examined the factors limiting the adoption of advanced technology in maize cultivation in Kabale District, Southwestern Uganda, focusing on socio-economic constraints and the role of policy interventions. Despite the potential benefits of advanced agricultural technologies, such as improved yields and sustainability, their adoption in Kabale District remains low. Socioeconomic and demographic factors, including farmers' education levels, income, access to credit, and extension services, significantly influence the adoption rates. Previous research highlights that limited financial resources and insufficient knowledge about the benefits and usage of advanced technologies hinder their widespread adoption among smallholder farmers. The role of policy interventions in facilitating the uptake of advanced technology practices is also a critical aspect of this study. Government policies and programs designed to support agricultural innovation, such as subsidies for technology acquisition, training programs, and improved access to markets, play a crucial role in enhancing technology adoption. However, the effectiveness of these interventions in Kabale District has been inconsistent, often hampered by inadequate implementation and lack of awareness among farmers. This research aimed to assess the existing policy framework and its impact on promoting advanced agricultural technologies in maize farming. By analyzing the socioeconomic barriers and evaluating the effectiveness of policy interventions, this study provided comprehensive insights into the challenges and opportunities for improving technology adoption in maize cultivation in Kabale District. The findings were expected to inform policymakers and stakeholders about the necessary steps to enhance the adoption of advanced technologies, thereby boosting maize productivity and ensuring sustainable agricultural development in the region.